The Relationship between Carotid Atherosclerosis, Inflammatory Cytokines, and Oxidative Stress in Middle-Aged and Elderly Hemodialysis Patients. (25th September 2013) - Ren, Hongqi; Zhou, Xuan; Luan, Zhiyong; Luo, Xiaomei; Han, Shujing; Cai, Qing; Rui, Wang; Li, Yan
Abstract : Objective . To identify the relationship between microinflammation, oxidative stress, and carotid arterial stiffness in hemodialysis patients. Methods . The CAS β and PWV obtained by ultrasound technology were used to assess carotid arterial stiffness. We divided the patients into either the CAS group or the non-CAS group based on the presence or absence of CAS. The parameters of ALB, Ca, P, TC, HDL, LDL, TG, glucose, creatinine, and hs-CRP levels were routinely tested in both groups of patients. The levels of TNF- α, IL-6, and 8-isoprostane F2 α were measured by ELISA. Results . A total of 42 patients were enrolled in the CAS group and 20 patients were enrolled in the non-CAS group. No significant differences between the CAS group and the non-CAS group were observed with respect to age, dialysis duration, DBP, BUN, Cr, TC, TG, HDL, LDL, and Hb. However, SBP, pulse pressure, and 8-isoprostane levels of the CAS group were higher than those of the non-CAS group. The hs-CRP, TNF- α, and IL-6 levels were elevated in both groups but showed no significant differences. Conclusions . Maintenance of hemodialysis patients exhibits a microinflammatory state that may lead to atherosclerosis. The roles of hypertension and oxidative stress may be more important.